2014
DOI: 10.2519/jospt.2014.4760
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Kinematics Pre– and Post–Thoracic Thrust Manipulation in Individuals With and Without Shoulder Impingement Symptoms: A Randomized Controlled Study

Abstract: Shoulder pain is a common and debilitating condi tion, and its prevalence is second only to low back pain. 9,42,52,63 Shoulder im pingement syndrome (SIS) is the most frequently encountered shoulder condition and accounts for 44% to 65% of all shoulder pain. 63 A greater amount of scapular internal rotation, as well as a lesser amount of scapular upward rotation and posterior tilt during arm elevation, has previously been documented in individuals with symptoms of SIS compared to asymptomatic individuals. [35]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 65 publications
5
78
1
Order By: Relevance
“…Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24]. Of these studies, only Mintken et al examined pain and shoulder ROM as outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24]. Of these studies, only Mintken et al examined pain and shoulder ROM as outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, using single or short interventions to the thoracic spine and the upper ribs show conflicting immediate- [22][23][24]26] and short-term results [13,25] in patients with shoulder pathology. Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in all 3 of these, only 1 SMT session was included and only short-term effects on pain were measured, with patients whose mean age was in the early 30s. [58][59][60] Only 1 of these trials 54 reported on adverse events, and in that case, there were none.…”
Section: Shoulder Impingement Syndromementioning
confidence: 99%
“…One of these was on LLLT 51 ; 1 on MT, specifically cervical mobilization 53 ; and 1 on spinal manipulation. 58 Engebretsen et al 55 reported that 2 patients in the ESWT group dropped out because of pain, with 1 crossing over to the supervised exercise group, and that 1 patient in the supervised exercise group reported increased pain. 55 Rhon et al 64 reported that in their trial of MT PT compared with CSIs, transient pain from the injection was the only adverse event reported.…”
Section: Adverse Events Reported In Rctsmentioning
confidence: 99%